Perubahan Berat Badan Balita Gizi Kurang Usia 1-4 Tahun Yang Diberikan Kukis Bekatul dan Kulit Pisang Di Desa Gebangmalang Kecamatan Mojoanyar Kabupaten Mojokerto - Susanti, Ika Yuni; Wijayanti, Krisdiana (Jurnal Pengabdian kepada Masyarakat Khaira Ummah, 2024)
Malnutrition status among children under five in Indonesia is still a serious problem faced today. The problem of malnutrition that occurs in children under five can be handled by providing additional food (PMT). This additional food can be obtained from local food ingredients which are easy to obtain and have economic value. The aim of the research was to conduct an analysis of the effect of giving rice bran cookies and banana peels on weight gain in malnourished toddlers aged 1-4 years in Gebangmalang Village, Mojoanyar District, Mojokerto Regency. The type of research is an experiment using a Completely Randomized Design (CRD) using two treatment groups (C1 and C2). The first stage is to carry out an acceptability test to find out which cookies are most liked and carry out an analysis of the nutritional content contained in the cookies. The next stage was to intervene by providing 50 grams of cookies for 28 days to see changes in the weight of malnourished toddlers aged 1-4 years. The research uses Prettest-Posttest Group Design. Research analysis using the Krusskal Wallis test showed that there was a difference between the acceptability of rice bran cookies and banana peel cookies with a value of ρ<0.05. Furthermore, based on the Mann Whitney test, it shows that C2 cookies are proven to be the most preferred cookies compared to C1 cookies with a value of ρ<0.05. Banana peel cookies contain nutrients including macro nutrients and micro nutrients including protein, calcium, ferrous and vitamin A per 100 grams of cookies. Based on the results of the independent T-test, it shows that there is a difference in the weight gain of malnourished toddlers aged 1-4 years in the intervention group and the control group with a value of ρ<0.05, while the average weight gain of malnourished toddlers aged 1-4 years in The intervention group was higher when compared to the control group with an average weight gain ratio in the intervention group of 5.3 while the weight gain in the control group was 1.3. Providing additional food as part of treating malnutrition in children aged 1-4 years can be done by providing cookies with the addition of economical local food ingredients. It is hoped that these cookies can be an alternative for dealing with malnutrition in children under five.